ANALISIS PENGARUH LINEARISASI CHORD LOKAL PADA DAERAH UJUNG BILAH DAN PERTENGAHAN BILAH TERHADAP KOEFISIEN DAYA UNTUK TURBIN ANGIN SKALA MIKRO MENGGUNAKAN SIMULASI CFD - Fransisco Jeremy Ginting (2021)
To find the optimum linearization, the method that is generally carried out is by testing linearization from the base of the blade to the tip of the blade. If this method is carried out it will take quite a long time. Thus, in this study we propose a new method that focuses on linearization near the blade tip. Chord linearization in the region near the tip results in a larger power coefficient than the mid chord region of the wind turbine blades because the region near the tip has greater wind speed than the mid region of the wind turbine blades. Then a CFD (Computational Fluid Dynamic) simulation is performed on 2 types of linearization (linearization at the tip and middle of the blade) and 2 different chord distribution methods (Betz and Schmitz) with different wind speeds and different TSR (Tip Speed Ratio). The results of the CFD simulation show that blade with 45% Betz chord linearization (at mid of the blade) produces a lower power coefficient than 75% Betz (at tip of the blade). However, the 45% Schmitz chord linearization produces a greater power coefficient than the 75% Schmitz chord linearization.